In vitro comparison of Günther Tulip and Celect filters. Testing filtering efficiency and pressure drop. Issue 3 (5th February 2015) - Nicolas, M.; Malvé, M.; Peña, E.; Martínez, M.A.; Leask, R.
Abstract In this study, the trapping ability of the Günther Tulip and Celect inferior vena cava filters was evaluated. Thrombus capture rates of the filters were tested in vitro in horizontal position with thrombus diameters of 3 and 6 mm and tube diameter of 19 mm. The filters were tested in centered and tilted positions. Sets of 30 clots were injected into the model and the same process was repeated 20 times for each different condition simulated. Pressure drop experienced along the system was also measured and the percentage of clots captured was recorded. The Günther Tulip filter showed superiority in all cases, trapping almost 100% of 6 mm clots both in an eccentric and tilted position and trapping 81.7% of the 3 mm clots in a centered position and 69.3% in a maximum tilted position. The efficiency of all filters tested decreased as the size of the embolus decreased and as the filter was tilted. The injection of 6 clots raised the pressure drop to 4.1 mmHg, which is a reasonable value that does not cause the obstruction of blood flow through the system.